Intraluminal Delivery of Simvastatin Attenuates Intimal Hyperplasia After Arterial Injury. (July 2019) - Helkin, Alex; Bruch, David; Wilson, David R.; Gruessner, Angelika C.; Bader, Rebecca R.; Maier, Kristopher G.; Gahtan, Vivian
Introduction: Oral statins reduce intimal hyperplasia (IH) after arterial injury by only ∼25%. Alternative drug delivery systems have gained attention as carriers for hydrophobic drugs. We studied the effects of simvastatin (free vs hyaluronic acid-tagged polysialic acid–polycaprolactone micelles) on vascular smooth muscle cell (VSMC) migration, VSMC proliferation and intimal hyperplasia. We hypothesized both free and micelle containing simvastatin would inhibit VSMC chemotaxis and proliferation, and local statin treatment would be more effective than oral in reducing IH in rats following carotid balloon injury. Methods: VSMCs pretreated with free simvastatin (20 minutes or 20 hours) or simvastatin-loaded micelles underwent chemotaxis and proliferation to platelet-derived growth factor. Next, rats that underwent balloon injury of the common carotid artery received statin therapy—intraluminal simvastatin-loaded micelles prior to injury, periadventitial pluronic gel following injury, or combinations of gel, micelle, and oral simvastatin. After 14 days, morphometric analysis determined the –intimal to medial ratio. Findings were compared to controls receiving oral simvastatin or no statin therapy. Statistical analysis was by analysis of variance for the in vitro experiments and a factorial general linear model for the in vivo experiments. Results: The simvastatin-loaded micelles and free simvastatin inhibited VSMC chemotaxis (54%-60%). IH was induced in all injured vessels. Simvastatin in pluronic gel or micelles reduced IH compared to untreated controls (0.208 ± 0.04 or 0.160 ± 0.03 vs 0.350 ± 0.03, respectively); however, neither gel nor simvastatin-loaded micelles were superior to oral statins (0.261 ± 0.03). Addition of oral statins or combining both local therapies did not provide additional benefit. Micelles were the single greatest contributing factor in IH attenuation. Conclusions: Intraluminally or topically delivered statins reduced IH. The efficacy of single-dose, locally delivered statin alone may lead to novel treatments to prevent IH. The different routes of administration may allow for treatment during endovascular procedures, without the need for systemic therapy.